(untitled) (Ameghiniana, 2020)
The new coral Heteroamphiastrea loeseri gen. et sp. nov., Family Carolastraeidae, Superfamily Heterocoenioidea, is described from the lower Aptian of the Lindi region (Tendaguru area) in southeast Tanzania. The new genus is characterised by a cerioid colony type, an underdeveloped septal system with bilateral symmetry defined by a strong main septum with secondary outgrowths and the presence of a marginarium. Overall, this monospecific genus shows skeletal features of the family Carolastraeidae, but like other genera of the family, it shares some morphological features with the families Heterocoeniidae (Heterocoenioidea) and Amphiastreidae (Amphiastreoidea). Heteroamphiastrea gen. nov. exemplifies corals with relatively rare morphology. They are the most controversial Mesozoic corals without consensus on highrank taxonomy. Heterocoenioidea and Amphiastreoidea have been recently classified into the suborder Heterocoeniina, Amphiastreina or Pachythecaliina, separately or together. Further, they were classified into the Order Scleractinia or into the extinct Order Hexanthiniaria.